Gender Bias in Fairy Tales Narrative Analysis of The Folk Story Malin Deman and Puti Bungsu - Syahrul, Ninawati; Sunarti, Sastri; Atisah, Atisah (International Journal of Multidisciplinary Sciences, 2025)
The status and role of women in familial, social, and cultural contexts remain persistent themes in both modern and classical fiction, including traditional folk tales. For past generations, folk tales often served as a medium for expressing social realities and moral reflections, particularly concerning the position of women within the family. This research investigates the portrayal of women in the folk tale Malin Deman and Puti Bungsu, with the aim of describing and analyzing gender roles and biases embedded in the narrative. Using a qualitative method with a discourse analysis approach, the study relies on literature review and narrative analysis techniques, focusing on a feminist perspective. The results reveal three key findings. First, female characters are portrayed as passive, forgiving, non-aggressive, and aligned with traditional ideals of femininity. Second, these characters are depicted as incapable of altering their destinies without male intervention, reinforcing dependency. Third, women are shown as victims of male domination, abuse, and objectification. The study concludes that such representations reinforce entrenched gender stereotypes, promoting the ideal woman as beautiful, graceful, submissive, and helpless without male support. These portrayals pose a significant challenge to the feminist movement and the broader pursuit of gender equality in contemporary society.